Doktrin Sekolah Islam Terpadu Melalui Bina Pribadi Islami Dalam Membangun Karakter - Nurdin Rivaldy; Encep Syarifudin; Rijal Firdaos (STAI Terpadu Yogyakarta, 2024)
Islamic educational institutions develop along with modernity, quality, and uniqueness so that they can strengthen the Indonesian education system. Education has an important character in the national education system, including a network of integrated Islamic schools that emphasize the doctrine of Islamic personal development. This research aims to determine the function of the doctrine of developing Islamic personal development at SMAIT Al Fidaa Bekasi Regency. The study used a qualitative method with a literature study approach. Based on research findings, the doctrine applied is in line with the Islamic Personal Development Guidelines formulated and established by the Integrated Islamic School Network Team. This guide takes inspiration from the Al-Qur’am and Sunnah. Ritual practices of worship consist of the five daily fardhu prayers, sunnah prayers, dhuha prayers, tahajud prayers, tadarus, sunnah fasting, and sadaqah. Understanding and application of the Al-Quran by improving students' ability to read the Al-Quran (Tahsin Al-Quran). Involvement in community service by actively contributing to society, is the importance of Islamic personal development doctrine. The research implications of the doctrine of effective Islamic personal development will maximize the formation of Islamic character and personality to protect against the influence of negative globalization and the formation of responsible and democratic character. Interviews are needed for further research to obtain more precise data regarding the influence of Islamic personal development doctrine on students.